2007
DOI: 10.1136/ard.2006.060608
|View full text |Cite
|
Sign up to set email alerts
|

High IgA rheumatoid factor levels are associated with poor clinical response to tumour necrosis factor   inhibitors in rheumatoid arthritis

Abstract: According to the clinical response, anti-TNFalpha agents seem to reduce IgM, IgG and IgA rheumatoid factor levels. More interestingly, high pretreatment levels of IgA rheumatoid factor are associated with a poor clinical response to TNFalpha inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
84
4
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(98 citation statements)
references
References 41 publications
9
84
4
1
Order By: Relevance
“…Recently, anti-citrullinated protein antibodies (ACPAs) have been shown to be more specific for RA (2). The presence of RF and ACPA autoantibodies is associated with disease progression (3) and responsiveness to treatment with antirheumatic drugs (4,5). Also, animal studies have shown that B cells are necessary for the development of arthritis and influence its severity (6).…”
mentioning
confidence: 99%
“…Recently, anti-citrullinated protein antibodies (ACPAs) have been shown to be more specific for RA (2). The presence of RF and ACPA autoantibodies is associated with disease progression (3) and responsiveness to treatment with antirheumatic drugs (4,5). Also, animal studies have shown that B cells are necessary for the development of arthritis and influence its severity (6).…”
mentioning
confidence: 99%
“…Therefore the increased severity of disease associated with the presence of RF IgA seems not to be attributable to these cytokines [33,34]. Accordingly, no correlation was found between serum IL-6 or BLyS levels and the levels of total or IgA-specific RF.…”
Section: Discussionmentioning
confidence: 90%
“…Evidence in the literature indicates that people with RA positive for RF IgA show more aggressive disease [33,34]. Furthermore, RF IgA seems to have a greater role in predicting the development of RA than RF IgM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with our findings implicating IgA RF more than IgM RF, Mikuls et al [36] found an association between CS and high serum IgA RF but not IgM RF in African Americans with RA. It has been shown in RA that high pretreatment levels of IgA RF are associated with a poor response to TNF inhibitors [37] and it has also been shown that smokers are poor responders to TNF inhibitors [38], thus, it is likely that the IgA RF link to smoking is the explanation for the former. Since our studies show a correlation between IgA RF and LD, this may also be a marker of relevance to follow in smokers.…”
Section: Discussionmentioning
confidence: 99%